PELATIHAN PENGOLAHAN LIMBAH SAYURAN RUMAH TANGGA MENJADI PUPUK ORGANIK CAIR (POC) DI KELURAHAN SASAKE, LOMBOK TENGAH - Nurlita Lestariani (LPPM IAI Muhammadiyah Bima, 2026)
Liquid organic fertilizer (POC) is a type of liquid fertilizer derived from organic materials that is easily absorbed by plants, thereby increasing soil fertility while also serving as an environmentally friendly solution to reduce dependence on chemical fertilizers. Training activities on processing POC from vegetable waste in Sasake Village were carried out using the Asset-Based Community Development (ABCD) method through the stages of counseling, practice, mentoring, and evaluation involving pre-tests, post-tests, and fermentation observations. The results of the activity showed an increase in the community’s knowledge and skills in converting vegetable waste into nutrient-rich, environmentally friendly POC that can be applied in agriculture. The three-week fermentation process demonstrated microbial development, indicating that it was running optimally. This training not only succeeded in reducing organic waste problems but also supported community independence, sustainable agriculture, and environmental conservation.